2021
DOI: 10.6007/ijarbss/v11-i8/10422
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Technology Acceptance Model (TAM) and Trust in Influencing Online Purchase Intention During the Covid-19 Pandemic: Empirical Evidence from Malaysia

Abstract: Online purchasing has been embraced by customers due to its convenience and the raising issues of the Covid-19 pandemic. This research examines the factors influencing customers' online purchase intention during the pandemic. Although a lot of research has been conducted regarding online purchasing, the factors influencing online purchase intention during the Covid-19 pandemic remain limited. Thus, this research incorporates the Theory of Acceptance Model and customer's trust to determine the factors influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Similarly, Collier and Sherrell (2009) stress the critical role of perceived customer convenience in self-service. Further studies by Singh et al (2017) and Leong and Chaichi (2021) highlight the significance of perceived convenience in shaping purchase intentions and consumer behavior, especially in online shopping and technology usage contexts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Collier and Sherrell (2009) stress the critical role of perceived customer convenience in self-service. Further studies by Singh et al (2017) and Leong and Chaichi (2021) highlight the significance of perceived convenience in shaping purchase intentions and consumer behavior, especially in online shopping and technology usage contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Singh et al (2017) found that elements such as security, convenience, and trust significantly influence consumer intentions, emphasizing the role of convenience in consumer behavior. Additionally, the Technology Acceptance Model (TAM) has shown that convenience plays a significant role in influencing online purchase intentions (Leong & Chaichi, 2021). These findings collectively highlight the critical importance of convenience in shaping customer intentions and behaviors.…”
Section: Perceived Convenience and Customer Intentionsmentioning
confidence: 94%
“…Enablers are defined as those factors which encourage the adoption of E-Commerce (Vinculum, 2020). The key drivers which arose consistently across several studies as enablers for E-Commerce adoption are convenience, time, and cost savings (Alqahtani, et al, 2014;Anas, et al, 2021;Leong & Chaichi, 2021;Farhang, et al, 2012;Vaicondam, et al, 2020).…”
Section: Enablers To E-commerce Adoptionmentioning
confidence: 94%
“…According to Jadil et al ( 2022), a significant correlation exists among convenience, perceived risk, trust, and online purchase intention, affirming the technology acceptance model. Leong and Chaichi (2021) found that the different elements of TAM, namely convenience, ease of use, usefulness, trust, and security, were significantly associated with online purchase intention. The adoption of this model was based on its inclination to digital technology.…”
Section: Literature Reviewmentioning
confidence: 96%